Interior Design of Omah Herbal Educational Tourism with Islamic Garden Concept in Kudus - Silfia Mona Aryani; Ananda Adityo Putri (TAMA: Journal of Visual Arts, 2025)
Omah Herbal is designed as a place for the community that provides education and recreation as well as conservation about medicinal plants. Indonesia boasts a very high biodiversity, resulting in a significant potential for the growth of medical plants. The utilization of medicinal plants as health maintenance needs to be developed because it does not cause harmful side effects compared to modern medicine, but people are less interested and do not know how to maintain medicinal plants. In addition, there is no facility that can support the delivery of information and education that is attractive to the community. By using the Islamic Garden concept, it is felt that it is in accordance with the characteristics of Kudus Regency, the facilities provided can optimize the five human senses so that it is more interactive with visitors or the community.